Tuntutan Tindak Pidana Penggelapan Terhadap Perbuatan Wanprestasi Dalam Hukum Perdata (Studi Putusan Pengadilan Negeri Tebing Tinggi No. 74/Pid.B/2019/Pn.Tbt Tertanggal 28 Mei 2019) - Juni Kristian Telaumbanua; Sunarmi Sunarmi; Madiasa Ablisar; Mahmud Mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2021)
Tebing Tinggi District Court Decision No. 74/Pid.B/2019/PN.Tbt dated May 28, 2019 where the defendant was charged for having committed late payment of bills after taking goods belonging to PT. Agung Bumi Lestari with arrears of Rp. 226,828,440.- which was agreed upon must be paid no later than 30 days after taking the goods. As a result, the defendant had to serve 2 months in prison. Therefore, it is necessary to study the boundaries that distinguish between default and the criminal act of embezzlement in the agreement and the application of default and embezzlement in the decision of the Tebing Tinggi District Court No. 74/Pid.B/2019/PN.Tbt.